Spatio-temporal distribution of gelatinous zooplankton in tropical mangrove estuaries: environmental drivers and possible mangrove disturbance effects - Siti A.R. Balqis; Md Yusoff, Fatimah; Kamarudin, Norizah; Hassan, Mohd Zafri; Nishikawa, Jun (Elsevier, 2022)
The impacts of environmental changes and mangrove disturbance on the gelatinous zooplankton community structure were investigated monthly for one annual cycle at six stations in three estuaries in Matang, Malaysia. Tiram, Tinggi, and Sepetang estuaries were classified based on the Mangrove Quality Index (MQI) to represent the least (MQI 5 = excellent), moderately (MQI 4 = good), and highly disturbed (MQI 2 = bad) areas, respectively. Among the gelatinous zooplankton species, the holoplanktonic ctenophore, Pukia ohtsukai (formed 56%–58% of the total gelatinous zooplankton), was the most dominant species and showed increased densities with the increasing level of disturbance. On the other hand, a hydrozoan, Blackfordia sp. (39%–43%), which needs suitable substrates for the survival of polyploids, was found to be most abundant in the moderately disturbed area, indicating low densities in areas with too little or too much disturbance. Salinity, a parameter influenced by river discharge and tidal changes, was identified as the main environmental factor affecting the species' seasonal variability. The dry season was associated with an increase in gelatinous zooplankton density and prevalence of marine species. Also, factors related to water clarity (turbidity, transparency, and suspended solids) and nutrients (nitrogen and phosphorus) explained 91% of the variables that affected the gelatinous zooplankton community structure. The species diversity (H′) in the least and moderately disturbed areas were significantly higher than in the highly disturbed estuary. In contrast, the highest mean density was recorded in the highly disturbed estuary (34.4 ± 19.8 inds. m−3) followed by the moderately (21.6 ± 6.1 inds. m−3) and the least disturbed areas (9.7 ± 4.1 inds. m−3). The present study suggested that the gelatinous zooplankton biodiversity declines and the abundance escalates with increasing disturbance levels.